Nanotechnology‐Mediated Drug Delivery for the Treatment of Obesity and Its Related Comorbidities. Issue 12 (2nd April 2019) - Tsou, Yung‐Hao; Wang, Bin; Ho, William; Hu, Bin; Tang, Pei; Sweet, Sydney; Zhang, Xue‐Qing; Xu, Xiaoyang
Abstract: Obesity is a serious health issue affecting humanity on a global scale. Recognized by the American Medical Association as a chronic disease, the incidence of obesity continues to grow at an accelerating rate and obesity has become one of the major threats to human health. Excessive weight gain is tied to metabolic syndrome, which is shown to increase the risk of chronic diseases, such as heart disease and type 2 diabetes, taxing an already overburdened healthcare system and increasing mortality worldwide. Available treatments such as bariatric surgery and pharmacotherapy are often accompanied by adverse side effects and poor patient compliance. Nanotechnology, an emerging technology with a wide range of biomedical applications, has provided an unprecedented opportunity to improve the treatment of many diseases, including obesity. This review provides an introduction to obesity and obesity‐related comorbidities. The most recent developments of nanotechnology‐based drug delivery strategies are highlighted and discussed. Additionally, challenges and consideration for the development of nanoformulations with translational potential are discussed. The overall objective of this review is to enhance the understanding of the design and development of nanomedicine for treatments of obesity and related comorbidities. Abstract : Obesity is a serious health issue affecting humanity on a global scale and can increase the risk of chronic diseases, such as heart disease and type 2 diabetes. This review discusses how nanotechnology can overcome current limitations and provide insights into the design and development of nanotechnology in the treatment of obesity and its related comorbidities.